ไฮโดรดีออกซิจิเนชันของกรดปาลมิติกบนตัวเร่งปฎิกิริยาซัลไฟด์ของ Ni-Mo และ Co-Mo แบบไม่มีตัวรองรับ - ศักดิพัฒน์ เวียงเกตุ (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
Palm oil from biomass fast pyrolysis or liquefaction usually consists of high oxygen content compounds (10-50 wt%), especially palmitic acid in palm oil. Therefore, the oxygen in palmitic acid could be removed in the form of water via hydrodeoxygenation (HDO). Catalysts containing Mo as an active element and Ni or Co as a promoter have been used intensively for HDO process. This research work is to investigate the hydrodeoxygenation of palmitic acid over unsupported Ni-Mo and Co-Mo sulfide catalysts. The parameters of study were catalysts, mole ratio of Ni-Mo and Co-Mo, concentration of reactant, temperature, pressure and reaction time. Experimental results show that the main products were n-alkanes (C14, C15 and C16). Increasing temperature enhanced decarboxylation and decarbonylation pathways, whereas increasing pressure increased the contribution of hydrodeoxygenation pathway. However using Ni-Mo sulfide catalyst gave a higher C16 selectivity and C16 yield than Co-Mo sulfide catalyst. Based on this research, the appropriate catalyst and conditions were Ni/(Ni+Mo) ratio of 0.2, reactant concentration of 1.5 wt%, temperature of 320 oC, pressure of 70 bar and reaction time of 60 min. that give high palmitic acid conversion (95.2 %), C16 selectivity (78.5 %) and C16 yield (65.6 %) .